An exploration of the perspectives of individuals and their caregivers on pressure ulcer/injury prevention and management to inform the development of a clinical guideline. Issue 1 (February 2022) - Haesler, Emily; Pittman, Joyce; Cuddigan, Janet; Law, Susan; Chang, Yee Yee; Balzer, Katrin; Berlowitz, Dan; Carville, Keryln; Kottner, Jan; Litchford, Mary; Moore, Zena; Mitchell, Pamela; et al.
Abstract: Background: Consumer engagement is a requirement of high quality clinical guidelines. Developing strategies to engage consumers and incorporate the perspectives of individuals with or at risk of pressure ulcers/injuries and their informal caregivers was one priority in the recent update of the EPUAP/NPIAP/PPPIA's Prevention and Treatment of Pressure Ulcers/Injuries: Clinical Practice Guideline . Aims: The aims were to determine the goals of individuals and caregivers for pressure ulcer/injury care, priorities for pressure ulcer/injury education and biggest problems related to pressure ulcers/injuries. Methods: An online, anonymous, international 10-item survey, accessible in nine languages was provided to individuals and their caregivers from April to October 2018. Descriptive statistics were used for quantitative data and a thematic analysis approach was used to analyse qualitative data. Results: There were 1233 individuals from 27 countries who completed the survey. Overall, individuals and caregivers had similar goals of care. Reducing the size of pressure ulcer/injury was selected more often as a care goal than complete healing. Individuals, compared to caregivers, considered managing pain more important. Qualitative data analysis identified five themes including knowledge, attitudes, and skills; risk factors for pressure ulcer/injury; accessing pressure ulcer/injury care; quality of life for patients and caregivers; and the pressure ulcer/injury. Conclusions: The consumer survey provided consumer engagement and perspective that was incorporated into guideline development, including consideration during evaluation of the relevance and acceptability of recommendations, and assignment of recommendation strength ratings. Highlights: Consumer engagement is an important consideration in contemporary clinical guideline development. A global survey was successful for incorporating perspectives of people with pressure injuries into a clinical guideline. Patients and their caregivers have similar care goals, but they may not reflect the same goals as health professionals. People with pressure injuries place high importance on information about facility-level pressure injury prevention plans.